PENGEMBANGAN MEDIA TUMBUH ANGGREK DENGAN MENGGUNAKAN KOMPOS - Nastiti Siswi Indrasti, dan Rio Reyno Elia (Jurnal Teknologi Industri Pertanian, 2004)
ABSTRACTCompost can be utilized as organic fertilizer and orchid’s growth media as well. In general, the objective of this research was to develop orchid's growth media from compost. The specific objectives of this research was : 1) to conduct the composting process using windrow techniques from buffalo manure, rice straw, coffee hull and leaf. 2) to investigate the effect of the compost and clay mixture, heating time and temperature to the physical and nutrient quality of the orchid’ growth media.The orchid's growth media consist of compost, clay and water  as raw material. The dimension of the orchid’s media was 10 x 10 x 4 Cm3. The orchid's growth media was made through manual's forming process and heating in oven. The used experimental design was completely randomized block factor design with two times replication. The ratio of compost to clay was 2:3; 2:2 and 3:2; the heating time factor was 2, 3 and 4 hours, and the heating temperature factor was 70, 80 and 90 oC. The best combination treatment was achieved by a mixture of compost and clay with the ratio of 2:2, heating time of 2 hours at 70 oC . The best combination treatment showed the value of pressure of 16,95 Kgf/Cm2; weight of 504,45 g; N-Total 0,68 %; P2O5 0,26 % and K2O 1,74 %.Key words :  Compost, Windrow Techniques, Orchid’s Growth  Media, Clay